1998
DOI: 10.1007/bf02821936
|View full text |Cite
|
Sign up to set email alerts
|

Controlled multicentre study of the influence of subcutaneous recombinant human erythropoietin on anaemia and transfusion dependency in patients with ovarian carcinoma treated with platinum-based chemotherapy

Abstract: This randomised controlled multicentre trial evaluated the effectiveness of recombinant human erythropoietin (rhEPO) in preventing anaemia and reducing the need for blood or erythrocyte transfusion in 122 ovarian cancer patients receiving platinum-based chemotherapy. The patients were randomly allocated to receive rhEPO 150 U/kg or 300 U/kg subcutaneously, three times a week, or open control. Patients also received up to 6 cycles of carboplatin or cisplatin, alone or in combination with other cytotoxic agents.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
49
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 19 publications
5
49
0
Order By: Relevance
“…Furthermore, epoetin b was well tolerated and was significantly superior to standard care in increasing Hb concentrations, irrespective of the type of tumour, or the presence and nature of chemotherapy. The findings are consistent with those reported in other clinical studies of epoetin (Case et al, 1993;Cascinu et al, 1994;Henry and Abels, 1994;Dammacco et al, 1998;Nowrousian, 1998;ten Bokkel Huinink et al, 1998;Ludwig, 1999).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, epoetin b was well tolerated and was significantly superior to standard care in increasing Hb concentrations, irrespective of the type of tumour, or the presence and nature of chemotherapy. The findings are consistent with those reported in other clinical studies of epoetin (Case et al, 1993;Cascinu et al, 1994;Henry and Abels, 1994;Dammacco et al, 1998;Nowrousian, 1998;ten Bokkel Huinink et al, 1998;Ludwig, 1999).…”
Section: Discussionsupporting
confidence: 93%
“…Thus, blood transfusions should be reserved for cases of lifethreatening anaemia. In contrast, treatment with recombinant human erythropoietin (epoetin) leads to a long-lasting increase in the number of erythroid progenitor cells and red blood cell count, and is effective and safe for the alleviation of anaemia and transfusion requirements in patients with cancer (Cazzola et al, 1995;Rose et al, 1995;Dammacco et al, 1998;ten Bokkel Huinink et al, 1998). Epoetin also improves quality of life (QoL) in anaemic cancer patients; however, only a few randomised studies have shown this (Dammacco et al, 2001;Littlewood et al, 2001;Ö sterborg et al, 2002), with most data coming from large, nonrandomised, community-based studies Demetri et al, 1998;Gabrilove et al, 2001).…”
mentioning
confidence: 99%
“…61 Recombinant Epo (epoetin) and its somewhat longer acting form (darbepoetin) are being used increasingly at the clinical level in ovarian cancer patients and other cancer patients as well. A randomized, controlled multicenter trial of Epo to prevent anemia and reduce red blood cell transfusions in 122 ovarian cancer patients receiving platinum-based therapy reported good Epo efficacy that was well-tolerated, 62 although more recently a ''definitive'' phase III trial has been called for. 63 A correlation between anemia and decreased survival in ovarian cancer has been described.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 2297 patients in the analysis, 35% had non-myeloid haematological malignancies (mainly non-Hodgkin's lymphoma or multiple myeloma) and 65% had solid tumours (most commonly primary malignancies of the breast, head and neck, colon/rectum and ovary). Other than the slightly higher proportion of patients in the epoetin group with ovarian carcinoma as a result of the three arm design of the study by ten Bokkel Huinink et al (1998), no clinically relevant differences between the groups were noted.…”
Section: Baseline Characteristics and Follow-upmentioning
confidence: 82%